Heuristics for an Integrated Maintenance and Production Scheduling Problem on Parallel Machines with Stochastic Failures and Non-Resumable Jobs - Wiebke von Hoyningen-Huene (ZBW - Leibniz-Informationszentrum Wirtschaft, 2015)
Maintenance activities can have a large impact on the performance of a production process and promised delivery dates. Therefore, maintenance and production planning should be handled as an integrated problem. In this paper, the problem of scheduling n jobs on m identical parallel machines is solved such that the expected makespan is minimised. The machines are affected by stochastic machine failures which are assumed to result in long production stops. To avoid this, preventive maintenance activities are planned beforehand. If a failure cannot be averted, a corrective maintenance has to be performed. Furthermore, it is assumed that jobs, interrupted by machine failure, have to be repeated (non-resumable case). In this paper, three construction heuristics and an Ant Colony System (ACS) algorithm are developed for solving this integrated problem. The excellent performance of the ACS as well as the benefit solving the problem in an integrated manner instead of sequentially, is shown in a numerical study.
Keywords: 650; Parallel Machine Scheduling; Maintenance; Stochastic Failures; Non-Resumable Jobs; Ant Colony System